Within the social world : - Chin, Jeffrey (Pearson, 2008)
This anthology contains original and classic essays on social psychology from sociological perspectives. Classic and original readings address two major emphases within social psychology:symbolic interactionism and how social structures impact the lives of individuals. Introductions to each chapter are written by the authors, who are sociologists. The authors help situate the essays within the broader field of social psychology and link them to other articles in the text